2012
DOI: 10.1038/jid.2011.446
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 and ST2 in Atopic Dermatitis: Expression Profiles and Modulation by Triggering Factors

Abstract: In the acute phase of atopic dermatitis (AD), T-helper type 2 (Th2) cytokines characterize the inflammatory response in the skin. IL-33 is a new tissue-derived cytokine, which is mainly expressed by cells of barrier tissues, and is known to activate Th2 lymphocytes, mast cells, and eosinophils. IL-33 signals through a receptor complex consisting of IL-33-specific receptor ST2 and a co-receptor IL-1RAcP. As IL-33 is known to promote Th2-type immunity, we examined expression profiles of IL-33 and its receptor co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
303
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(324 citation statements)
references
References 47 publications
14
303
1
6
Order By: Relevance
“…These results indicate that IL-33 released upon mechanical skin injury can potentially target ST2-expressing cells, including MCs, at distant sites. AD often involves more than 10% of the total body surface area, and the median IL-33 level in AD patients serum is more than 10 folds that of healthy controls 16 , 46 . These observations suggest that the mouse model we have used to examine the role of IL-33 in food anaphylaxis following EC sensitization is relevant to patients with AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that IL-33 released upon mechanical skin injury can potentially target ST2-expressing cells, including MCs, at distant sites. AD often involves more than 10% of the total body surface area, and the median IL-33 level in AD patients serum is more than 10 folds that of healthy controls 16 , 46 . These observations suggest that the mouse model we have used to examine the role of IL-33 in food anaphylaxis following EC sensitization is relevant to patients with AD.…”
Section: Discussionmentioning
confidence: 99%
“…Forced IL-33 local overexpression by keratinocytes induces ADlike symptoms 15 . IL-33 levels are increased in the skin lesions and serum of patients with AD 16 , 17 and in mouse skin following EC sensitization with OVA 16 . A polymorphism in the gene coding for ST2, a chain of the IL-33 receptor (IL-33R), has been associated in humans with AD 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, IL-33 has been shown to downregulate serum-induced expression of human β defensin-2 in keratinocytes (24). Immunohistochemical staining showed an increased number of IL-33 + cells among suprabasal keratinocytes and an increased staining of ST2, an IL-33 receptor, among dermal infiltrates in AD lesions (25). IL-25 increases the expression of IL-5 and IL-13 in TSLP-DC-activated T cells (26).…”
Section: Keratinocyte Dysfunctions In Admentioning
confidence: 99%
“…Lesional human AD skin has elevated expression of epithelial cell-derived cytokines that promote ILC2 responses including IL-25, IL-33, and TSLP (Soumelis et al 2002;Hvid et al 2011;Deleuran et al 2012;Savinko et al 2012), and ILC2s have been identified in both murine and human skin and are enriched in the lesional skin of human AD patients (Kim et al 2013a;Roediger et al 2013). Although IL-33 has emerged as the dominant cytokine in the activation of ILC2s from murine lung , human blood, and nasal polyps (Mjosberg et al 2012), the original studies identifying skin ILC2s found that murine skin ILC2s are IL-33-and IL-25-independent but dependent on TSLP for their activation during murine AD-like disease (Kim et al 2013a).…”
Section: Ilc2s In the Skin Atopic Dermatitismentioning
confidence: 99%